KERAGAAN AGRIBISNIS DAN PROSPEK PEMASARAN KOPI RAKYAT - Ahmad Choiri; Aryo Fajar Sunartomo (University of Jember, 2008)
This research was conducted in Sidomulyo village Silo subdistrict, Garahan village Silo subdistrict and Gelang village Sumberbaru subdistrict Jember regency which have been deliberately determined (purposive method) by considering those have a potential plantation, especially the citizenry coffee’s commodity. The research method which is used is a descriptive method and analytical method. Analysis method which is used is a Trend analysis by Least Square Method. The result of research shows (1) The average of citizenry coffee farmer’s age in Sidomulyo village, Garahan village and Gelang village is productive age. (2) The using of input in the production of citizenry coffee farmer in Sidomulyo village, Garahan village and Gelang village for a seed comes from government aids, own producing/other group and market. (3) The capital source of citizenry coffee farmer in Sidomulyo village, Garahan village ang gelang village is an own capital and comes from family loan or the other farmer, (4) The kind of citizenry coffe protection plant in Sidomulyo village, Garahan village and Gelang village is a dadap, lamtoro, sengon laut, avocado, glirisidae, coconut and banana, (5) The buyer of citizenry coffee produce is a merchant of compiler and grocher by selling system of large quantity and the merchant who determinates selling prices, (6) The trend of selling citizenry coffee in Sidomulyo village have a positive direction, by the selling prediction for 2008 and 2009 is increase, and (8) The selling trend of citizenry coffee in Gelang village has a negative direction, by selling prediction for 2008 and 2009 is decrease. Key words : Agribusiness Performance and Marketing Prospect of Citizenry coffee